Numerical study on the seismic performance of precast segmental concrete columns under cyclic loading - Li, C.; Hao, Hong; Bi, K. (Pergamon, 2017)
To accelerate construction speed, precast segmental column is becoming more and more popular in recent years due to its obvious advantages in saving construction time, reducing site disruption and controlling construction quality. However, the applications are still limited primarily in low seismic areas because its performance under earthquake loading is not well known yet. Many experimental studies have been carried out to investigate the seismic performance of segmental columns under cyclic loading. Due to the complexity in modelling such structures, numerical study of precast segmental columns subjected to seismic loads is limited. In this paper, three dimensional (3D) finite element (FE) models for two precast segmental columns are developed to predict the responses of such columns under lateral cyclic loading. The numerical models are first validated against the cyclic test results and then used to perform parametric studies. The influences of five parameters including bonding condition of the tendon, total initial axial forces level, confinement of the segments, number of segments, and energy dissipation (ED) bars on the performance of segmental columns are systematically investigated. Moreover, columns with shape memory alloy (SMA) bars are also investigated to increase the energy dissipation capacity and reduce the residual drift of the segmental columns. It is found that both mild steel and SMA bars can increase the energy absorption capacity of the column, but the SMA bars can minimize the residual drift due to its innate mechanical property. This study clearly identifies the influences of different factors on the performance of segmental columns. The developed numerical model can be used in the future studies to predict the seismic responses of structures with segmental columns.